2021
DOI: 10.1172/jci.insight.150483
|View full text |Cite
|
Sign up to set email alerts
|

TNFRSF13B genotypes control immune-mediated pathology by regulating the functions of innate B cells

Abstract: Host genes define the severity of inflammation and immunity but specific loci doing so are unknown. Here we show that TNF receptor superfamily member 13B ( TNFRSF13B ) variants, which enhance defense against certain pathogens, also control immune-mediated injury of transplants, by regulating innate B cells’ functions. Analysis of TNFRSF13B in human kidney transplant recipients revealed that 33% of those with antibody-mediated rejection (AMR) but fewer than 6% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…61 TNFRSF13B is one of the most polymorphic genes in humans, leading Cascalho and colleagues to test whether TNFRSF13B alleles might determine the magnitude of innate B-cell responses and graft outcome. 65 Their study showed that human kidney transplant recipients with missense mutations in TNFRSF13B comprised 33% of those with AMR, but only <6% of those with stable graft function had TNFRSF13B missense mutations. These observations raised the possibility that wild-type (WT) levels of TACI were protective and, conversely, reduced TACI resulted in more aggressive alloreactivity.…”
Section: Tnfrsf13b Polymorphisms Control T-independent Antibody Respo...mentioning
confidence: 99%
See 3 more Smart Citations
“…61 TNFRSF13B is one of the most polymorphic genes in humans, leading Cascalho and colleagues to test whether TNFRSF13B alleles might determine the magnitude of innate B-cell responses and graft outcome. 65 Their study showed that human kidney transplant recipients with missense mutations in TNFRSF13B comprised 33% of those with AMR, but only <6% of those with stable graft function had TNFRSF13B missense mutations. These observations raised the possibility that wild-type (WT) levels of TACI were protective and, conversely, reduced TACI resulted in more aggressive alloreactivity.…”
Section: Tnfrsf13b Polymorphisms Control T-independent Antibody Respo...mentioning
confidence: 99%
“…To define the mechanisms for these unexpected observations, de Mattos Barbosa et al used a mouse cardiac transplant model to show that allografts in Tnfrsf13b -mutant recipients underwent early and severe AMR. 65 The increased propensity for developing AMR in Tnfrsf13b -deficient mice was not caused by increased alloantibodies but rather was associated with decreased “natural” IgM production.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed investigation further revealed that mice and human subjects with defects in or absence of TACI function exhibit defective control of T cell-dependent B cell responses [ 39 ], suggesting the receptor might act in the opposite ways in T cell-independent and T cell-dependent responses. More recent investigation reveals that TACI limits clonal expansion and affinity maturation of T cell-dependent B cell responses [ 40 ] but also that the mixture of innate and elicited B cell responses in host defense and transplantation can have a greater biological impact than the intensity of one or another type of response [ 38 , 41 ].…”
Section: Tnfrsf13b or Taci Complexity And Functionmentioning
confidence: 99%